An Adaptive Method for Gait Event Detection of Gait Rehabilitation Robots - Ye, Jing; Wu, Hongde; Wu, Lishan; Long, Jianjun; Zhang, Yuling; Chen, Gong; Wang, Chunbao; Luo, Xun; Hou, Qinghua; Xu, Yi (Frontiers in Neurorobotics, 2020)
Accurate gait event detection is necessary for control strategies of gait rehabilitation robots. However, due to personal diversity between individuals, it is a challenge for robots to detect gait event at various stride frequencies. This paper proposes a novel method for gait event detection of a gait rehabilitation robot using a single inertial sensor mounted on the thigh. A self-adaptive threshold for detecting heel strike is obtained in real-time via a linear regression model. Observable thresholds for toe off detection are constant at various stride frequencies. Experiments are conducted based on twenty healthy subjects and six hemiplegic patients wearing a gait rehabilitation robot and walking at various kinds of stride frequencies. The experimental results show that the proposed method can detect heel strike and toe off gait events within an average 2% stride temporal errors and never miss the two-gait events detection. Compared to the conventional thresholding method, this work presents a simple and robust application for gait event detection in healthy and hemiplegic subjects by one inertial sensor. The linear regression model can be applicable to different subjects walking at various stride frequencies.